Incarvillea compacta Maxim ameliorates inflammatory response via inhibiting PI3K/AKT pathway and NLRP3 activation - Zhang, Ji; Feng, Yujing; Han, Shengqiang; Guan, Xueting; He, Ziliang; Song, Chao; Lv, Lingyun; Luo, Qiaoyu (Frontiers in Pharmacology, 2022)
Incarvillea compacta Maxim is a traditional Tibetan medicine used to treat inflammation-related diseases, such as pneumonia, fever, jaundice, and otitis media. However, no studies have examined its anti-inflammatory mechanism. To validate the anti-inflammatory activity of I. compacta extract (ICE) and its protective effect on acute alcoholic gastritis, Phytochemicals of I. compacta were identified using Ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS). Lipopolysaccharide (LPS)-induced RAW 264.7 macrophages were used in vitro along with an in vivo a mouse acute gastritis model. Pro-inflammatory mediators and cytokines were measured using the Griess reagent and Cytometric bead array (CBA) assay. Furthermore, inflammation-related molecules were analysed by Western blotting, RNA-Seq, and real-time quantitative PCR (RT-qPCR). The experimental results revealed that ICE decreased the nitric oxide (NO), IL-6, MCP-1, and TNF-α levels in LPS-stimulated RAW 264.7 cells, and downregulated the expression and phosphorylation of PDK1, AKT, and GSK3β. Moreover, ICE also downregulated the activation of NLRP3. The RNA-Seq analysis revealed that 340 differentially expressed genes (DEGs) response to ICE treatment was enriched in several inflammation-related biological processes. The results of the in vivo mouse acute gastritis model showed that ICE significantly reduced inflammatory lesions in the gastric mucosa and remarkably downregulated the expression of iNOS, TNF-α, IL-1β, and IL-6 mRNA in gastric tissue. Therefore, the results of this study obtained scientific evidence supporting the use of I. compacta.